Dietary profile of n-3 series LC-PUFAs in rainbow trout under regular stripping condition: Semen production and quality, hepato-somatic index, haemato-immunologic values, oxidative stress and fatty acid composition of liver, muscle and semen - Yonar, Serpil Mise; Koprucu, Kenan; Ozcan, Sinan (Wiley, 2020)
In this study, the semen production and quality, hepato-somatic index, haemato-immunologic values, oxidative stress and the fatty acid contents in liver, muscle and semen of rainbow trout fed diets supplemented n-3 series long-chain polyunsaturated fatty acids (LC-PUFAs) under regular stripping condition were investigated. For this aim, three diets (Control, D1 and D2) were prepared. These diets were contained n-3 LC-PUFAs (as a percentage of dietary total fatty acid) at 3.14%, 7.84% and 13.63% respectively. Experimental fish were fed with the control and test diets. The highest hepato-somatic index, spermatologic (semen pH and volume, sperm motility and density), haematologic (haematocrit value, haemoglobin, erythrocyte count, corpuscular volume, haemoglobin and its concentration in corpuscular), immunologic (nitroblue tetrazolium activity, leucocyte count, phagocytic index, protein and immunoglobulin [IgM] in total plasma) and antioxidants (reduced glutathione, catalase, glutathione peroxidase and superoxide dismutase) values were found in fish fed the D2, D1 and control diets respectively (p < 0.01). Increase in the dietary n-3 LC-PUFAs was not significantly (p > 0.01) increased the oxidative stress (malondialdehyde) in fish. The results indicated that the n-3 LC-PUFAs at 13.63% level of total fatty acid in the diet could increase the semen production and quality, hepato-somatic index, haematologic and immunologic values, and the n-3 LC-PUFA contents in liver, muscle and semen of rainbow trout broodstock under regular stripping condition.
Keywords: fatty acids; haematology; immunity; oxidative stress; rainbow trout; semen